Political Inequality of Law: A comparative study of migrant electoral rights in Mercosur countries - Modolo, Vanina Edit (2011)
International Journal of Sociology (ISSN 0020-7659). The International Journal of Sociology is indexed/abstracted in: Association for Asian Studies; Bibliography of Asian Studies; De Gruyter Saur; Dietrich´s Index Philosophicus; IBZ - Internationale Bibliographie der Geistes-und Sozialwissenschaftlichen Zeitschriftenliteratur; Internationale Bibliographie der Rezensionen Geistes- und Sozialwissenschaftlicher Literatur; EBSCOhost; Academic Search Complete; Business Source Corporate; Communication & Mass Media Complete; Current Abstracts; FRANCIS; Political Science Complete; Public Affairs Index; Russian Academy of Sciences Bibliographies; SocINDEX; TOC Premier; E-psyche; Gale; Academic OneFile; Criminal Justice Collection; Expanded Academic ASAP; General OneFile; InfoTrac Custom; Psychology Collection; H.W. Wilson; Social Sciences Index; National Library of Medicine; PubMed; OCLC; ArticleFirst; CSA Sociological Abstracts; Electronic Collections Online; ProQuest; CSA Social Services Abstracts; Environmental Sciences and Pollution Management; FRANCIS; PAIS International; Periodicals Index Online; Risk Abstracts; Worldwide Political Science Abstracts; Taylor & Francis; Educational Research Abstracts Online; and Studies on Women and Gender Abstracts. In 1991, Argentina, Brazil, Uruguay, and Paraguay signed the Asunción Treaty, whose purpose was to set up a common economic market, Mercosur (an acronym meaning Mercado Común del Sur, or Southern Cone Common Market). Mercosurean migrants receive special treatment in the bloc. They enjoy broad legal protection and benefits in comparison to other aliens and have been incorporated into labor, civil, and social rights regimes. However, some political rights, electoral rights in particular, have not been improved. I examine political inequality before the law in a critical analysis of electoral legislation in the original four Mercosur states, focusing on migrants rights to vote and to be candidates in local, regional, and national elections. The main findings of this study are that (a) electoral laws consistently discriminate against migrants, (b) each country has its own legal framework for discrimination, and (c) these discriminatory laws constitute gaps in the social and economic protections provided by Mercosur.